BUYING EXPERIENCE: THE IMPACT OF TRUST AND SATISFACTION OF GRAB FOOD CUSTOMERS IN SURABAYA - Iristian, Jovi; Irdiana, Sukma (Universitas Dr. Soetomo, 2019)
This study aims to determine and explain the influence of buying experience on customer trust and customer satisfaction in Grab Food customers in Surabaya. The selection of the location of this study considered that the customers who usually bought food using Grab Food were customers whose market segments were in the big city community. The exogenous variables in this study were buying experience, while the endogenous variables were trust and customer satisfaction. The type of research used was explanatory research. The sample were 140 respondents with a sampling technique using purpose sampling. The data collection method used a questionnaire. The validity test and reliability test were used to test the instrument. The result of testing the instrument indicated that the entire instrument was valid and reliable. Data analysis used descriptive analysis and path analysis. The results of this study indicated that buying experience had a significant effect on trust with the contribution of 26.9%. Buying experience had a significant effect on customer satisfaction with a contribution of 22.1%, and trust had a significant effect on customer satisfaction with a contribution of 17.1%.This study aims to determine and explain the influence of buying experience on customer trust and customer satisfaction in Grab Food customers in Surabaya. The selection of the location of this study considered that the customers who usually bought food using Grab Food were customers whose market segments were in the big city community. The exogenous variables in this study were buying experience, while the endogenous variables were trust and customer satisfaction. The type of research used was explanatory research. The sample were 140 respondents with a sampling technique using purpose sampling. The data collection method used a questionnaire. The validity test and reliability test were used to test the instrument. The result of testing the instrument indicated that the entire instrument was valid and reliable. Data analysis used descriptive analysis and path analysis. The results of this study indicated that buying experience had a significant effect on trust with the contribution of 26.9%. Buying experience had a significant effect on customer satisfaction with a contribution of 22.1%, and trust had a significant effect on customer satisfaction with a contribution of 17.1%.Â Keywords: Buying Experience, Trust, Customer Satisfaction